2018
DOI: 10.2495/sdp-v13-n1-121-129
|View full text |Cite
|
Sign up to set email alerts
|

The awareness of integrated project delivery and building information modelling - facilitating construction projects

Abstract: Construction projects are complex undertakings, which involve many different parties striving towards successful completion. Effective and efficient processes are based on collaboration with an integrated project delivery approach, the project team working together as a cohesive unit towards a common goal. However, the current procurement system adopted creates fragmentation of the design and construction teams, which results in projects being delivered late, constructability issues, final project cost exceedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 3 publications
(3 reference statements)
4
15
0
Order By: Relevance
“…Also, the outcomes do not support studies that identify contractual matters (Fish, 2011), lack of trust (Pishdad-Bozorgi and Beliveau, 2016) or contractual features of the immediate context (Rached et al, 2014) as major inhibitors to widespread IPD use. In essence, these findings echo the observations by Govender et al (2018), who argued that stakeholders have a reasonable awareness of the advantages and benefits of IPD, and as such, major barriers to IPD do not, in fact, stem from a lack of understanding of IPD methodology or its advantages.…”
Section: Discussion Of the Findingssupporting
confidence: 77%
“…Also, the outcomes do not support studies that identify contractual matters (Fish, 2011), lack of trust (Pishdad-Bozorgi and Beliveau, 2016) or contractual features of the immediate context (Rached et al, 2014) as major inhibitors to widespread IPD use. In essence, these findings echo the observations by Govender et al (2018), who argued that stakeholders have a reasonable awareness of the advantages and benefits of IPD, and as such, major barriers to IPD do not, in fact, stem from a lack of understanding of IPD methodology or its advantages.…”
Section: Discussion Of the Findingssupporting
confidence: 77%
“…Unfortunately, in developing nations especially Africa little is known about the adoption of construction 4.0 technologies among construction stakeholders. Most studies conducted in Africa particularly in South Africa are concentrated on the adoption of building information technology such as Govender et al (2018) and Saka and Chan (2019) while neglecting other industry 4.0 technology. This has created a gap in the study on the willingness and challenges confronting construction stakeholders towards adopting construction 4.0 technologies for construction projects in South Africa.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, several studies have highlighted the need for more research on BIM implementation in South Africa (Chimhundu 2015;Froise 2014;Mtya 2019). Several more recent studies also found that BIM uptake in South Africa is low compared to other countries (Govender 2018;Meno 2020;Mtya & Windapo 2019). As a result, the competitiveness of the South African construction industry (SACI) is potentially under threat, and international companies are in an advantageous position to take work from local companies (Froise 2014).…”
Section: A Proposal To Facilitate Bim Implementation Across the South...mentioning
confidence: 93%
“…Some countries, such as the United Kingdom (UK), have recognised the economic value of BIM and put in place strategies to facilitate BIM implementation (HM Government 2015; Royal Institution of Chartered Surveyors 2020). However, South Africa has yet to reach a high level of BIM maturity across the industry (Akintola et al 2020;Govender 2018;Mtya 2019). Although a handful of larger AECO firms have gained some BIM capabilities, BIM implementation in South Africa is neither widespread nor optimal (Akintola et al 2017;Kiprotich 2014;Mtya 2019).…”
Section: Introduction Backgroundmentioning
confidence: 99%